Zeeman gyrotropic scatterers: Resonance splitting, anomalous scattering, and embedded eigenstates - Gangaraj, S Ali Hassani; Monticone, Francesco; Valagiannopoulos, Constantinos (Nanomaterials and Nanotechnology, 2018)
Anomalous scattering effects (invisibility, superscattering, Fano resonances, etc) enabled by complex media and metamaterials have been the subject of intense efforts in the past couple of decades. In this article, we present a full analysis of the unusual and extreme scattering properties of an important class of complex scatterers, namely, gyrotropic cylindrical bodies, including both homogeneous and core–shell configurations. Our study unveils a number of interesting effects, including Zeeman splitting of plasmonic scattering resonances, tunable gyrotropy-induced rotation of dipolar radiation patterns as well as extreme Fano resonances and non-radiating eigenmodes (embedded eigenstates) of the gyrotropic scatterer. We believe that these theoretical findings may enable new opportunities to control and tailor scattered fields beyond what is achievable with isotropic reciprocal objects, being of large significance for different applications, from tunable directive nano-antennas to selective chiral sensors and scattering switches, as well as in the context of nonreciprocal and topological metamaterials
Keywords: Scattering; gyrotropy; Zeeman effect; plasmonic resonances; embedded eigenstates